HIV/AIDS prevalence among adolescents in Igbo-Eze South Local Government Area, Enugu State, and the need for faith-based interventions - Favour Chukwuemeka Uroko; Goodness Chimeremma Ike (HIV & AIDS Review. International Journal of HIV-Related Problems)
Introduction This study investigated the prevalence of human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) among adolescents in Igbo-Eze South Local Government Area (LGA) of Enugu State, Nigeria. Igbo-Eze South is an area in Enugu State that has received little attention from scholarly community, especially with regards to HIV/AIDS due to its geographical location and spiritual makeup. This study was aiming to defy the odds by exploring the immediate and remote factors, which indicate the commonness of HIV/AIDS among adolescents in the community.